Crop of organic arugula in greenhouse using high seedlings from different volumes of substrates - Pinto, Geazí Penha; Tomio, Denis Borges; Ferreira, Regina Lúcia Felix; Araújo Neto, Sebastião Elviro de; Souza, Luís Gustavo de Souza e; Silva, Nilciléia Mendes da (Comunicata Scientiae, 2021)
The objective of this study was to evaluate the substrate volume in the production of high seedling and its cultivation on organic arugula components production in protected cultivation. The high seedling planting evaluation occurred over different substrate volumes (50, 100, 200, 300, and 400 cm³) in two plastic-cover protected environments (with and without anti-insect screen mech 50) using randomized blocks as experiment design with four replications, and 16 plants per plot. The seedlings produced with 280.3 cm³ of substrate provided the highest fresh mass and plant productivity. The highest dry aerial part mass of the plant was obtained from seedlings produced with 316.5 cm³ of substrate. The productivity, fresh mass, and dry matter mass of leaves higher in a covered greenhouse, however, with a higher total cost of production (R $ 6.81 m²), lower net revenue (R $ 6.52 m²), and profitability index 110%. The use of high seedling produced with 300 or 400 cm³ of substrate reduces the crop time regardless of the culture environment within eight days; however, the highest profitability is obtained with volumes of 200 cm³ (R$ 0.37 m² day-¹), and 100 cm³ (R$ 0.36 m² day-¹) of substrate for environments with and without insect screen, respectively.